Developing hidden curriculum scale of medical faculty - Ercan, İlker and Yüksel, Sedat and Özkaya, Güven and Ocakoğlu, Gökhan and Yüksel, Asuman and Uncu, Yeşim (Cerrahpaşa Medical Journal, 2013)
Objectives: Present study aims to develop a scale that can assist in detecting the hidden curriculum in medical faculties. Methods: Developing scale was applied to 185 students. After repeated experiments, reliability and validity analysis and factor analysis was applied to draft scale at the beginning, scale was consist of 25 items as a standart scale. Results: Scale items was grouped in seven factors and reliability coefficients of these subscales was between 0.53-0.85. Cronbach alpha reliability coefficient of Medical Faculty Hidden Curriculum Scale consisted of 25 items was 0.8945. Scale was having construct and content validity. Conclusion: Medical Faculty Hidden Curriculum Scale was developed which have “scientific thinking, discussion and searching skill”, “utilization of stage”, “physician skills”, “instructor objectivity”, “being decisive, tenacious and sistematic” and “having not rote learning” subscales.